Transition Curves for Roads Designers Manual - Muthanna Husham , Alfityan; A., Zulkiple
in this manuscript we introduce an introduction about this thesis with the title Transition Curves for Roads (Designers Manual), includes the main headlines that the thesis will handle to be as a designers manual, also we introduce the equations of a transition curve which can be used by designers with a table of Excel software to facilitate the obtaining of the information needed for the designers